2013
DOI: 10.1080/10810730.2012.757389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Responsibility Attribution and Message Source on Young Adults' Health Attitudes and Behaviors

Abstract: This study investigated the effect of message attributes on responses to health messages. The authors examined 3 variables--responsibility attribution (individual vs. social), source (personal blog vs. online magazine), and illness (stigmatized vs. nonstigmatized)--for effects on young adults' health-related attitudes and behaviors. Responsibility attributions influenced attitudes about individual responsibility for health but did not alter participants' behavioral intentions. Further, individuals exposed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As such, the medical cannabis literature echoes findings from previous studies that have found stigma to be associated with specific health conditions. Individuals suffering from a stigmatized health condition may be perceived as less intelligent, less deserving of sympathy, and less credible than people with nonstigmatized health conditions (Boiarsky, Rouner, & Long, ). Specifically, people living with HIV/AIDS suffer from a high level of stigmatization (Herek, Capitanio, & Widaman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, the medical cannabis literature echoes findings from previous studies that have found stigma to be associated with specific health conditions. Individuals suffering from a stigmatized health condition may be perceived as less intelligent, less deserving of sympathy, and less credible than people with nonstigmatized health conditions (Boiarsky, Rouner, & Long, ). Specifically, people living with HIV/AIDS suffer from a high level of stigmatization (Herek, Capitanio, & Widaman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Malle (2004) reported that framings around specific incidents and individuals were more likely to result in audiences’ perceptions of attributions of responsibilities focusing on the characteristics of individuals. Boiarsky et al (2013) found that personal LOR stories significantly increased the public’s perception that individuals are responsible for given issues, whereas social LOR stories do not have the same effect. Major (2009) reported that thematic stories about lung cancer and obesity increased individuals’ attribution of social responsibility.…”
Section: Discussionmentioning
confidence: 89%
“…This trend is particularly manifest in the case of various health issues, including cancer. Even if the existing research has not yet fully clarified the ways news media contents influence audiences' attribution of responsibility (Boiarsky, Rouner, & Long, 2013;Major, 2009), it is nonetheless evident that news media play a critical role in shaping public perceptions and opinions of who is responsible for causing or solving social problems (Iyengar & Kinder, 1987;Semetko & Valkenburg, 2000). Most previous studies have found more news stories emphasizing personal-level responsibility than society-level responsibility for various health issues, including cancer (S. H. Kim & Willis, 2007;Seale, 2002;Wright, Sparks, & O'Hair, 2008).…”
mentioning
confidence: 99%
“…Second, researchers have examined young adults’ responses to different types of responsibility attribution in health messages, but they generated mixed results. For example, Boiarsky et al (2013) found that individual-responsibility messages generated a slightly greater effect on young adults than social-responsibility messages. Vorpahl and Yang (2018), however, found that attributing the causes of HPV transmission to “others” resulted in stronger persuasive outcomes than those emphasizing the responsibilities of “self.” More research is needed to explore the effects of responsibility attribution on this social group regarding COVID-19 vaccination.…”
Section: Literature Reviewmentioning
confidence: 99%